Is there a European language history? - Mattheier, Klaus J. (Multilingua, 2010)
The thoughts on a language history within a European context sketched out here represent an attempt to extend the concepts of regional and particularly national language history by adding a third dimension: transnational language history in Europe. After a few general thoughts on the extended area of research, in which so-called external language history is linked to historical pragmatics and particularly to historical sociolinguistics, four research paradigms are outlined: the comparative sociolinguistic approach, the concept of the cycle of communication, the language contact approach and the socio-historical and cultural-historical approach.
Online veröffentlicht am 14. Januar 2011
Gesehen am 25.05.2023